Stereoselective Biginelli-like reaction catalyzed by a chiral phosphoric acid bearing two hydroxy groups - Hu, Xiaoyun; Guo, Jianxin; Wang, Cui; Zhang, Rui; Borovkov, Victor (Beilstein Journal of Organic Chemistry, 2020)
To develop new efficient stereoselective catalysts for Biginelli-like reactions, a chiral phosphoric acid bearing two hydroxy groups derived from ʟ-tartaric acid was successfully synthesized via highly regioselective transformations of enantiopure 1,1,4,4-tetraphenylbutanetetraol. The obtained catalyst effectively catalyzed Biginelli-like reactions with moderate to good enantioselectivities. Control experiments indicated that the presence of the two hydroxy groups were indispensable for achieving a high enantioselectivity.
Keywords: asymmetric Biginelli-like reaction; chiral 1,1,4,4-tetraphenylbutanetetraol; chiral phosphoric acid